2019
DOI: 10.3390/ijerph16183413
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Profile and Reproductive Decisions of Women Undergoing Pregnancy Termination for Medical Reasons—A Cross-Sectional Study

Abstract: Background: The study aims to define the profile of women who decide to exercise their right to terminate a pregnancy and their future reproductive plans. Methods: Patients found eligible for termination for medical reasons between 2014 and 2016 were asked to complete an anonymous survey consisting of sixty questions examining the determinants of the decision to terminate a pregnancy. In total, 150 completed surveys were returned (62.5%). Results: Environmental factors, such as age, education, place of residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The results of Zareba et al (2019) showed that the environmental factors of age, education, place of residence, marital status, and the economic situation did not affect the process of decision-making [25]. According to the results of our study, the age of the mother, the job the mother and spouse, family income level, and the type of pregnancy (wanted or unwanted) had no relationship with the scores of legal abortion ethical aspects (P>0.05), that the results were in line with the results of the mentioned study.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Zareba et al (2019) showed that the environmental factors of age, education, place of residence, marital status, and the economic situation did not affect the process of decision-making [25]. According to the results of our study, the age of the mother, the job the mother and spouse, family income level, and the type of pregnancy (wanted or unwanted) had no relationship with the scores of legal abortion ethical aspects (P>0.05), that the results were in line with the results of the mentioned study.…”
Section: Discussionmentioning
confidence: 99%
“…Such a phenomenon might result from the regionalization of facilities offering prenatal diagnostics and pregnancy terminations. They are not performed in numerous provinces, because physicians invoke the conscience clause [ 24 ]. Pregnancy terminations due to fetal defects are performed on a larger scale in few centers in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about possible complications associated with the delivery of a pregnancy carried to term, prognosis concerning fetal defects, and the procedure itself contribute to the changes of one's viewpoint on the appropriate indications for pregnancy termination [5]. It is also important to offer adequate contraceptive counseling to the woman during her request for abortion, in order to avoid other unplanned pregnancies [33].…”
Section: Of 10mentioning
confidence: 99%
“…In some cases, pregnancy may be unwanted or there may be particular conditions such as fetal abnormalities or pregnancy complications that make abortion necessary [3,4]. Abortion is a very complex phenomenon, both for women and for healthcare professionals [5]. A physician's decision to perform a pregnancy termination is affected by several factors, including the law, the healthcare organization, accessibility of health services, and the social situation of the country [6].…”
Section: Introductionmentioning
confidence: 99%